A single vial is enough in the absence of endoscopic suspected intestinal metaplasia – less is more!. (4th May 2019) - Castro, Rui; Esposito, Gianluca; Libânio, Diogo; Afonso, Luís; Annibale, Bruno; Dinis-Ribeiro, Mário; Pimentel-Nunes, Pedro
Abstract: Background: For the correct staging of chronic atrophic gastritis (AG) and gastric intestinal metaplasia (GIM) at least 4 biopsies are recommended: 2 from the antrum/incisura and 2 from the body sent in two different vials. As virtual chromoendoscopy with narrow-band-imaging (NBI) is valid both in the diagnosis and staging of GIM, it is reasonable to question the need to separate biopsy samples in all procedures. Aims : To evaluate if biopsy samples can be placed in the same vial without implications in the diagnosis and follow-up of the patient, if during gastroscopy no typical endoscopic pattern of GIM with NBI is observed. Methods : Multicentre prospective study of a consecutive sample of patients ( n = 183) submitted to gastroscopy using NBI with no superficial neoplastic lesions and no suggestive areas of GIM. Biopsies of both antrum/incisure and body were performed in all patients and samples were placed in the same vial for histologic assessment [according to OLGA (operative link for gastritis assessment) and OLGIM (operative link for gastric intestinal metaplasia)], blinded to endoscopic features. Results : In all patients, OLGA and OLGIM calculation was possible as the pathologists could distinguish biopsy samples from antrum/incisure from those of gastric body. The negative predictive value was 100% for advanced stages of GIM or AG as 179 (98%) patients presented OLGIM 0 and only 4 (2%) presented OLGIM I. Regarding AG, 150 (82%) presented OLGA 0, 23 (13%) OLGA I and 10 (6%) OLGA II. Conclusion : In the absence of a typical endoscopic pattern of GIM using NBI, it is effective to place biopsies' specimens in the same vial (for Helicobacter pylori diagnosis) or even to abstain from biopsies as no single patient with significant changes seems to be missed. This change in clinical practice can have a significant impact on endoscopy costs.